Perubahan Ekonomi Global dan Neraca Pembayaran - Nurbetty Herlina Sitorus; Dian Fajarini (Departement of Mathematics Education, 2023)
The balance of payments is a reflection that can be used as a benchmark for Indonesia's welfare and economic performance. This research aims to find out how the global economy and macroeconomic fundamentals, represented by the variables world GDP, world inflation, real exchange rates and world exports and imports of goods and services, affect Indonesia's balance of payments. The data used is time series data from 2016 to 2022. The method used in this research is the Error Correction Model (ECM) method using unit root and cointegration tests.